Control Interno de los Bienes de Uso Administrativo Del Gobierno Autónomo Descentralizado Municipal del Cantón Vinces. - Santana Correa, Priscila Alexandra (2020)
The present case study is based on the Internal Control of Assets of Administrative use in the Municipal Decentralized Autonomous Government of the Canton Vinces, by means of which it is intended to carry out an analysis of the different processes of the administration of the assets, which has place in the cellars of the aforementioned institution. Internal control is very important because through this, it allows the entity's resources to be safeguarded, thus avoiding material losses, whether due to fraud or negligence. In the study carried out, it was observed that the institution does not apply a control in stocks through which it will allow it to effectively carry out the activities of reception, storage and dispatch of the merchandise. However, the disorder that has arisen in the inventories of said institution has been analyzed and evaluated in order to adequately improve the application of a rigorous internal control of said goods and processes. Therefore, the main objective is to indicate all the factors that cause a correct internal control not to occur in order to avoid massive losses of goods, to carry out the correct registration of inventories in the system and to make use of the policies established in the manuals so that in this way the goods are controlled efficiently and to avoid the generation of more shortcomings that affect said area.